THE INFLUENCE OF BRAND AMBASSADOR TOWARDS PURCHASE DECISION THROUGH BRAND IMAGE AS THE MEDIATOR AT WHITELAB - Hanun Aisyah; Bulan Prabawani (Universitas Diponegoro, 2024)
The product of cosmetics and skincare sector is currently growing well in Indonesia. A growing number of people aware of how important it is to keep healthy skin, particularly women. Skincare manufacturers are competing to develop and supply products that may satisfy the demands of potential customers due to the increasing needs of the skincare market. One of Whitelab's marketing strategies is to increase product sales by utilizing brand ambassadors to attract consumer purchasing decisions. Whitelab collaborated with Sehun as a brand ambassador to release an exclusive collaboration package. But, Whitelab's position is still at the bottom of competitors who also use brand ambassadors as a promotion tool. Then, this research aims to know the influence of brand ambassador towards the customers purchase decision through brand image as the mediator at Whitelab, tested based on variables but explained through the influence of each dimension/indicator on each variable. The total sample in this research is 100 respondents with the sampling techniques is non-probability sampling which is purposive sampling. The data collection techniques are through questionnaire, literature review, and interview. The type of this research is explanatory research that processed used SmartPLS 3.2.9 software with the result indirect effects brand ambassador influences positive significantly on the customers purchase decision through brand image as the partial mediation. Recommendation for Whitelab company is expected to pay more attention to the brand ambassadors used, companies need to select local brand ambassadors.Keywords: Brand Ambassador, Brand Image, Purchase Decision